Perspektive raziskovanja etničnosti in manjšin v 21. stoletju - Rizman, Rudi (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2006)
PERSPECTIVES ON THE RESEARCH OF ETHNICITY AND MINORITIES IN THE 21ST CENTURY. The author seeks to identify the main substantive research topics that will most probably define and inform the research agenda concerning ethnicity and minorities in the 21st century. Researchers in this area need to reject those views, primarily post-modernist ones, which deny the academic validity and political urgency of ethnic and minorities' phenomena. Further discussion focuses on the following issues: on the multi-dimensional and complex nature of research in this area, on the limits of instrumental and reductionist approaches, the influences of uneven distribution of power and influences as far as ethnic groups and minorities is concerned, the substantial implications for ethnic structuration of societies as they are caused by the emergent and accelerating processes of globalization, on the necessity to recognize the autonomy of the spheres of state and ethnicicy alongside with their specific linkages, on deficiencies of the liberal understanding of ethnic issues, etc. The author warns before overoptimistic expectations that national or minority questions can be solved once and for all and thereby concludes with the assertion that relative and viable solutions in this area can be reached under condition that society further maintains and nurtures its diversity - ethnicity being one of its core constituants.
Keywords: manjšine; narodne manjšine; etničnost; 21.st.; globalizacija; globalization; raziskovanje